The role of tertiary education in intergrating professional contribution in the multi-disciplinary building design team - Whyte, Andrew (ACEN Incorporated, 2010)
The realisation of a client‘s brief in the construction industry requires the interaction of a range of specialist architectural, engineering and building professionals. If effective participation is sought to improve efficiency levels in multi-disciplinary building design-teams, motivational mechanisms (such as increased identification with disparate colleagues; over-arching goal acceptance; and, trust) are required to compliment expert technical input. There is a need perhaps to recognise that fulfilment of professional potential may best be found in combining particular skills efficiently in the participative building design-team. Findings from an attitude-scale of the construction professions are discussed in terms of the extent to which the values and expectations of organisational members influence the building design process and the final built product and, the extent to which addressing these variables at a tertiary educational stage, through structured cross-disciplinary project-work, has a potential to prepare practitioners for a more effectively integrated building industry.